Tourist activity: international and domestic diversification and the problem of social exclusion - Alejziak, Wiesław (Turyzm/Tourism, 2012)
This article presents the international and domestic diversification of tourist activity. In the former case, it focuses on analyses of the general level of tourist activity, expressed in the ‘tourist activity rate’, while with regards to the inhabitants of Poland, analyses were conducted on the diversification of tourist activity across various socio-demographic categories. For international comparisons, the wide-ranging research conducted by EUROSTAT in 2011 on representative samples of the inhabitants of 32 European countries was used. The diversification of Polish tourist activity in the context of social exclusion, on the other hand, is presented on the basis of the author's research and calculations. Statistical analyses were employed: Kendall's Tau-b rank correlation coefficient and cluster analysis.